On the track of visual style: a diachronic study of page composition in comics and its functional motivation. (May 2021) - Bateman, John A; Veloso, Francisco OD; Lau, Yan Ling
Page layout is one of the most salient features of graphic novels and comics that readers encounter: even before engaging with specific content, an overall impression of the page composition will have already been communicated. In the critical literature on comics and graphic novels, it is also commonly claimed that page composition plays a significant role for narrative construction, pacing, and other aspects of reception. However, in contrast to this prominence, methods for engaging systematically with the analysis of page design in comics and graphic novels are still in their infancy. Empirical studies of the workings of visual page composition are rarer still. In this article, the authors report results, drawing on a diachronic, corpus-based investigation of page composition that illustrates how it is beneficial to approach page composition employing methods from corpus linguistics and multimodality. They show not only that it is possible to isolate trajectories of change in composition over time but also that such studies can be used to provide evidence of functionally-motivated variation in compositional choices.